Dihliz Al-Ghazali: Seni Hibrida dalam Merumuskan Epistemologi Islam - Chafid Wahyudi (Proceedings of Annual Conference for Muslim Scholars, 2018)
The word dihliz often becomes a narrative of the sufism in the truth to find his God. Abu Hamid al-Ghazali in his al-Munqiz; “wa ma qabla dhalika ka al-dihliz li al-salik Ilaihi” [“And whatever precedes it, it is like dihliz (threshold position) for the seeker if it (God)’]. This word is not much to glance at, not even a lot of articulate it, on the contrary the translators only focus on the expression “seeker of it” (li al-salik Ilaihi), rather than the word dihliz itself. Dihliz in articulation is “threshold position.” It is an offer of an epistem that seeks to negotiate things that are seen as contradictory. In practice, subjectivity from subject autonomy, discourse of mediation, and hybrid and decolonization of knowledge. By being accepted as an Islamic epistemology provides the foundations of insight and reconciliation to bridge different religious traditions. His ideas can serve as a model and provide the foundations for an emancipatory and pluralism. In contrast to the epistemology of Islamization of science, there is a solid barrier between Islamic scholarship and Western scholarship.